Bukti Manfaat Aktivitas Fisik Terhadap Kesehatan dan Kebugaran: A Systematical Riview - Meylissa Meylissa; Dian Rahayu; Diana Lestari (Pusat riset dan Inovasi Nasional, 2025)
Background: Regular physical activity has a significant impact on improving the quality of health in all age groups. One of the main factors causing the increasing prevalence of Non-Communicable Diseases (NCDs) such as diabetes, heart disease, and obesity is lack of physical activity. Data from various studies show that increasing physical activity and fitness levels can reduce the relative risk of death by 20% to 35%. This condition shows that physical activity is not only important for maintaining fitness, but also has a vital role in preventing premature death caused by chronic diseases. Objective: This study aims to systematically examine the benefits of physical activity on health and fitness through a systematic review of 13 relevant scientific articles. Results: The findings show that regular physical activity can improve and maintain muscle and bone health, reduce the risk of chronic diseases such as diabetes, heart disease, and obesity, and reduce symptoms of mental disorders such as depression and schizophrenia. In addition, physical activity also plays a role in improving psychological well-being. Conclusion: Consistent physical activity contributes to the primary and secondary prevention of various chronic diseases, reduces the risk of premature death, maintains a balanced body composition, and supports optimal organ function. This results in a healthier, fitter body, and individuals being more productive in their daily activities.